2019
DOI: 10.1101/2019.12.19.882258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of the Reissner Fiber and increased URP neuropeptide signaling underlie scoliosis in a zebrafish ciliopathy mutant

Abstract: Cilia-driven movements of the cerebrospinal fluid (CSF) are involved in zebrafish axis straightness, both in embryos and juveniles [1,2]. In embryos, axis straightness requires ciliadependent assembly of the Reissner fiber (RF), a SCO-spondin polymer running down the brain and spinal cord CSF-filled cavities [3]. Reduced expression levels of the urp1 and urp2 genes encoding neuropeptides of the Urotensin II family in CSF-contacting neurons (CSF-cNs) also underlie embryonic ventral curvature of several cilia mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…It remains to be understood whether this difference in hydrocephalus prevalence among species relates to differences in susceptibility to stenosis of the aqueduct, in overall CSF dynamics and/or in additional genetic predisposition. Additionally, defects in motile cilia have been associated with scoliotic malformations of the spine in zebrafish, at larval, juvenile and adult stages [19,34,35,72,94,95]. We did not observe scoliosis in foxj1b, gmnc, as well as foxj1a+/-;foxj1b-/-and foxj1b;gmnc mutant animals, suggesting that body axis formation is not regulated by the ciliary mechanisms described in this work.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…It remains to be understood whether this difference in hydrocephalus prevalence among species relates to differences in susceptibility to stenosis of the aqueduct, in overall CSF dynamics and/or in additional genetic predisposition. Additionally, defects in motile cilia have been associated with scoliotic malformations of the spine in zebrafish, at larval, juvenile and adult stages [19,34,35,72,94,95]. We did not observe scoliosis in foxj1b, gmnc, as well as foxj1a+/-;foxj1b-/-and foxj1b;gmnc mutant animals, suggesting that body axis formation is not regulated by the ciliary mechanisms described in this work.…”
Section: Discussionsupporting
confidence: 49%
“…Loss of foxj1b and gmnc does not impact body axis and brain morphogenesis, but affects the size of brain ventricles Previous work using zebrafish revealed that motile cilia defects induce severe scoliosis of the spine [19] due to aberrations in Reissner fiber formation, impaired CSF flow, catecholamine transport and urotensin II-related peptide gene expression in spinal CSF-contacting neurons [34,36,[72][73][74]. To date, it remains unexplored which ciliated cell population contributes to this phenotype.…”
Section: Figure 6 Diversity Of Motile Ciliated Cells In the Adult Tementioning
confidence: 99%
“…In our enrichment analysis, dyneinassociated gene families were detected, which means that these pathways were also involved in the pathogenesis of AIS of Chinese cohort. The dysfunction of cilia was also suggested to be related to AIS susceptibility in several other studies (Grimes et al, 2016;Oliazadeh et al, 2017;Konjikusic et al, 2018;Van Gennip et al, 2018;Zhang et al, 2018;Vesque et al, 2019). Mutations in ptk7 or kif6, which affect the formation of ependymal cilia, induce IS-like scoliosis in zebrafish (Grimes et al, 2016;Konjikusic et al, 2018), implicating CSF flow as a crucial regulator of spine stability.…”
Section: Discussionmentioning
confidence: 85%
“…Faithful genetic models of scoliosis, which model aspects of AIS in zebrafish, have been described ( Kusumi and Dunwoodie, 2010 ; Boswell and Ciruna, 2017 ; Wu et al, 2019 ). Thus far, the etiology of scoliosis in these zebrafish models is associated with defects in the development of ependymal cell cilia and abnormal cerebrospinal fluid (CSF) physiology ( Grimes et al, 2016 ; Konjikusic et al, 2018 ), disassembly of the central canal resident glycoprotein structure called the Reissner fiber ( Lu et al, 2020 ; Rose et al, 2020 ; Troutwine et al, 2020 ), and alteration of neuropeptide signaling within the central canal ( Zhang et al, 2018 ; Vesque et al, 2019 ; Lu et al, 2020 ), which altogether appear to contribute to increased neuroinflammation ( Van Gennip et al, 2018 ; Rose et al, 2020 ). Given the increased incidence of variants in axonemal dynein assembly factors and axonemal dynein genes in our cohort, which are well established to be essential for cilia physiology, we set next out to test if these genes were essential for spine morphogenesis in zebrafish.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of foxj1b and gmnc does not impact body axis and brain morphogenesis but does affect the size of brain ventricles Previous work using zebrafish revealed that motile cilia defects on brain MCCs induce severe scoliosis of the spine (Grimes et al, 2016). Subsequent analysis attributed this deformity to aberrations in Reissner fiber formation, impaired CSF flow, catecholamine transport, and urotensin II-related peptide gene expression in spinal CSF-contacting neurons (Troutwine et al, 2020;Vesque et al, 2019;Rose et al, 2020;Zhang et al, 2018;Lu et al, 2020). Surprisingly, we did not observe axial malformations among foxj1b, gmnc, foxj1a+/À;foxj1bÀ/À, or foxj1b;gmnc double mutant adults (Figure 7A; embryonic lethality of foxj1aÀ/À animals prevented us from analyzing the homozygous mutants as adults).…”
Section: Cell Reportsmentioning
confidence: 99%